Amelioration of diethylnitrosamine (DEN) induced renal oxidative stress and inflammation by Carissa carandas embedded silver nanoparticles in rodents. (2021) - Singh, Deepika; Chaudhary, Deepak; Kumar, Vikas; Verma, Amita
Graphical abstract: Highlights: Phytofabricated silver nanoparticles (CCAgNPs) were biosynthesized and characterized. CCAgNPs were evaluated against diethylnitrosamine induced renal cancer. Silver nanoparticles have an antioxidant property. Silver nanoparticles unveiled a therapeutic effect against renal cancer in vivo . Abstract: Introduction: Inflammation and oxidative stress are the main factors ascribed with interruption in the process of renal tissue impairment. The toxicity of different types of nitrosamine is well recognized in animals and humans. Administration of the smallest quantities of diethylnitrosamine or dimethylnitrosamine either orally or parenterally results into renal damage. Therapeutic effects of phytofabricated silver nanoparticles of Carissa carandas aqueous extract has been scrutinised in current study for the assessment of renal cancer activity in animal model. Methodology: Phytofabricated silver nanoparticles were characterized by using different instrumentation. Nephroprotective activity of silver nanoparticles at different doses was evaluated against N-diethylnitrosamine (200 mg/kg b.w., intraperitoneal) in animal model. Serum and renal homogenate were taken to evaluate the renal toxicity markers, oxidative stress, and antioxidant parameter, proinflammatory cytokines and histopathological study. Result: Significant outcomes of silver nanoparticles in dose dependent manner down regulated the elevated serum marker, tumour marker enzymes and histopathology observation of repaired tissue assured the renal cancer activity in animals. In addition, profile of enzymatic and non-enzymatic antioxidant, proinflammatory cytokines and tumour promotion marker also favours the anticancer property of silver nanoparticles. Conclusion: The data of current study reveals silver nanoparticles ameliorates renal oxidative stress and carcinogenesis which was induced by N-diethylnitrosamine and accredited to antioxidant and anticancer activities of phytofabricated nanoparticles by biological approach.